Insular operculum disconnection and herniation into the parapharyngeal space due to a fetal Galassi Type III arachnoid cyst: a case report - Li, Ping; Zhang, Qin; Yang, Yuantao; Ji, Xinting; Zhao, Rui; Gu, Shuo (Frontiers in Neuroscience, 2024)
Arachnoid cysts (ACs) are frequently encountered as incidental findings in the brain, with most cases being asymptomatic and not requiring intervention. However, severe brain malformations caused by ACs are rare. In this study, we describe the case of an 8-day-old female infant with a left mandibular mass that was diagnosed as an insular operculum, which has become disconnected and herniated into the parapharyngeal space through an incompletely ossified greater wing of the sphenoid, caused by a fetal Galassi Type III AC. The newborn also exhibited left hearing impairment, which did not improve at the 6-month follow-up after the cyst peritoneal shunt. This report highlights that ACs that manifest during the early fetal period may protrude from the cranial cavity through an unossified skull, potentially affecting the development of brain tissues.